Determinant of credit risk of Islamic banks in Pakistan - Fazeelat Iqra Shaheen; Nadia Ameer Uddin Khan; Mirza Adnan Baig; Mohammad Muzammil (Future Business Journal)
Abstract This study aims to investigate the influence of macroeconomic variables and bank-specific factors on the credit risk of Islamic banking in Pakistan, through the panel data regression tools. The statistical tool which is applied to the research is ordinary least square (OLS) regression model. All the assumption to be fulfilled before using OLS. The secondary data have been taken from four (04) full-fledged Islamic banks in Pakistan, from 2007 to 2021. The focus of the research is to find the impact of macroeconomic variables like Gross domestic product, inflation, and growth in the interest rate and bank-specific factors like size, return on assets, loan loss provision, capital Adequacy ratio, and Asset quality to determine the credit risk (non-performing loans) of Islamic banks in Pakistan. The result of the ordinary least square (OLS) regression model is that loan loss provisions (LLP) have a positive and significant impact on credit risk (CR) and size of bank (S), and Capital adequacy ratio (CAR) have a negative and significant impact on credit risk (CR) of Islamic Bank of Pakistan. Inflation (INF) and Gross domestic product (GDP) have a positive and insignificant impact on credit risk (CR), and growth in interest rate (INT), return on assets (ROA), and asset quality (AQ) has a negative and insignificant impact on Credit risk (CR) of Islamic Bank of Pakistan. Therefore, Islamic banks should carefully examine their specific factors, i.e. LLP, S, and CAR to manage their credit risk, particularly in monitoring loans.